A Skin-depth Analysis of Integrins: Role of the Integrin Network in Health and Disease. (December 2013) - Hegde, Samarth; Raghavan, Srikala
Abstract In the skin epidermis, adhesion to the underlying basement membrane is mediated through trans-membrane integrin receptors. In addition to a structural role, integrins can signal in a bi-directional manner though the membrane and thus play a crucial role in cell adhesion, migration, proliferation, and differentiation. In this review we will discuss the role of integrins and their network of partner proteins in normal skin development, and how dysregulation influences disease states such as skin blistering disorders and cancers. We also discuss major integrin-specific therapeutic advances that have been made over the past few years in treating these skin disorders as well as targeting angiogenesis, neo-vasculature, and tumorigenesis.